A functional calculus for subnormal operators. - Conway, John B., 1939-; Olin, Robert F., 1948- (Memoirs of the American Mathematical Society, 1977)
Let S be a subnormal operator on a Hilbert space [script]H with minimal normal extension [italic]N operating on [italic]K, and let [lowercase Greek]Mu be a scalar valued spectral measure for [italic]N. If [italic]P[infinity symbol]([lowercase Greek]Mu) denotes the weak star closure of the polynomials in [italic]L[infinity symbol]([lowercase Greek]Mu) = [italic]L¹[infinity symbol]([lowercase Greek]Mu) then for [script]f in [italic]P[infinity symbol]([lowercase Greek]Mu) it follows that [script]f([italic]N) leaves [script]H invariant; if [script]f([italic]S) is defined as the restriction of [script]f([italic]N) to [script]H then a functional calculus for [italic]S is obtained. This functional calculus is investigated in this paper.